DINAMIKA PENENTUAN ARAH KIBLAT - Dwi Putra Jaya (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2017)
Abstract: To know the direction of Qiblah is already a lot of tools. Can be through measurements, can also use a prayer rug that has a compass Qiblah direction that is widely used in mosques. However, in order to attain the virtue of charity, it is necessary to make sure that the direction approached in the direction precisely facing the Temple. The way of determining the direction of the Qiblah for mosques has evolved in accordance with the development of knowledge held by Islamic societies, in the early stages using a very simple way, then progressed by using tools to measure it, among them Trigonometry, the shadow of the sun, compass magnet, transparent compass, compass Qibla, protractor, Rubu ‘mujayyab, string or thread, stick istiwa’ and waterpas, lot, elbow.